The effectiveness of mind mapping as a learning tool for office management and technology students / Nor Sabrena Norizan, Ahmad Fadhly Arham and Fatanah Jislan - Norizan, Nor Sabrena; Arham, Ahmad Fadhly; Jislan, Fatanah (Universiti Teknologi MARA, Selangor, 2022)
All educational system aims to improve students' ability to acquire information, as they are used to memorising facts instead of understanding and implementing the concept. Students must engage in a long-term process of individual learning. As a result, an approach known as mind mapping is contended to improve their individual ability to remember and recall things and improve their academic performance. Previous studies have proven the effectiveness of mind mapping for studying, summarising ideas, retaining, and retrieving information. Thus, the objective of this conceptual paper is twofold, which are to examine the importance of computerised mind mapping as a learning approach and to determine the effectiveness of computerised mind mapping among Office Management and Technology students. The questionnaires will be distributed to semester one students enrolled in the Personality Development course since mind mapping is covered in the syllabus. This data will be analysed using Statistical Package for Social Sciences (SPSS) 26.0 to determine the effectiveness of mind mapping for the students. It is believed that this study will identify the importance of computer mind mapping in enhancing the students' performance as positive evidence and outcomes of the past researchers are briefly discussed regarding the effectiveness of mind mapping. The researchers concluded with a rationale why computerised mind mapping works with the students, especially during this challenging COVID-19 pandemic.